Nonepileptic Seizures During Sleep - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Nonepileptic (psychogenic or pseudo) seizures (NESs) were documented by video-electroencephalographic monitoring during apparent sleep in 12 patients reported from New York University School of Medicine.